(3fhGRd GdbUQis - (3GdbUQj Hf eMeO Hf GdeNJGQ Hf YKeGf GdbUQjs
(3ChdgG (B:s
(3fhGRd GdeYGhVGJ (B: (3SDGd Yf Mce eG jaYd ai HdGOfG ef EecGf GdYHjO ef TQGA hfMhg, gd gh eefhY dbhdge (B: (3hdG jJcd ai Pdc Ydi ef dGjYQa GdCMcGe Ch jYQagG hjJSGgd HgG , hdGTc ai JSGgdge , EPG dGOjf dge s
(3BNQgG (B:s
(3SDGd Yf Mce ef ChUi aeLghd heYdhe , LhGHg JeJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HYV ChQGbgG eQbeIs
(3cJHJ HYV YHGQGJgG HGdMeQI s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3Gdabg GdESdGejs